Camera Trapping and Conservation in Lambir Hills National Park, Sarawak - Mohd-Azlan, J.; Engkamat, L. (National University of Singapore, 2006)
A rapid assessment using camera traps was carried out in Lambir Hills National Park from February 2004 to September 2004. In 1127 trap nights, six CamTrakker units and one DeerCam unit recorded a total of 225 wildlife photographs, which included seven orders, 11 families and 18 species of animals. Macaca nemestrina had the highest frequency of photo records with 63 exposures, while single exposures were recorded for Arctictis binturong, Echinosorex gymnurus, Prionodon linsang, Rheithrosciurus macrotis,Sus barbatus, and Macaca fascicularis. The rare Neofelis nebulosa was also recorded during this study. Activity patterns were calculated for five species. Low photo records of large mammals were noted and is believed to be caused by illegal hunting. The conservation of these species is discussed.